2014
DOI: 10.1016/j.ijpharm.2014.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characterization of d-mannitol polymorphs: The challenging surface energy determination by inverse gas chromatography in the infinite dilution region

Abstract: Nowadays, it is well known that surface interactions play a preponderant role in mechanical operations, which are fundamental in pharmaceutical processing and formulation. Nevertheless, it is difficult to correlate surface behaviour in processes to physical properties measurement. Indeed, most pharmaceutical solids have multiple surface energies because of varying forms, crystal faces and impurities contents or physical defects, among others. In this paper, D-mannitol polymorphs (α, β and δ) were studied throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 35 publications
4
27
1
Order By: Relevance
“…However, the pattern of peaks observed in the lyophilized samples was different to that from the crude ITZ. It has been shown by others (Cares-Pacheco et al, 2014;Grohganz et al, 2013;Kaialy and Nokhodchi, 2013;Lee et al, 2011) that the excipient mannitol is crystalline after lyophilized and our own results also showed this (data not shown). The contribution from mannitol in the ITZ-PBLA-Nanos explains why the peak pattern of the ITZ-PBLA-Nanos was different from that of the crude ITZ.…”
Section: Crystalline State Of Itzsupporting
confidence: 67%
“…However, the pattern of peaks observed in the lyophilized samples was different to that from the crude ITZ. It has been shown by others (Cares-Pacheco et al, 2014;Grohganz et al, 2013;Kaialy and Nokhodchi, 2013;Lee et al, 2011) that the excipient mannitol is crystalline after lyophilized and our own results also showed this (data not shown). The contribution from mannitol in the ITZ-PBLA-Nanos explains why the peak pattern of the ITZ-PBLA-Nanos was different from that of the crude ITZ.…”
Section: Crystalline State Of Itzsupporting
confidence: 67%
“…Polymorphic identity of the crystals obtained in this study was confirmed by comparing the PXRD pattern of different crystals obtained in this study with the predicted diffraction patterns that were generated using Reflux module in Materials Studio 5.5 (Accelrys Software Inc.). Furthermore, PXRD patterns obtained in this study for different polymorphs of D-mannitol was also compared with literature confirming the presence of all three different polymorphs of D-mannitol (16,33). The powder pattern of α polymorph was characterised by peaks at 2θ values 9.5°, 13.8°, and 17.4°.…”
Section: Characterisation Of D-mannitol Polymorphssupporting
confidence: 66%
“…Solvent and humidity induced transformation of crystal forms and limited success in reproducibly preparing different polymorphs has hindered the progress. Recently, CaresPacheco, et al have reported the surface energy heterogeneity of different polymorphic forms of D-mannitol (16). β and δ polymorphs of D-mannitol were reported to be energetically homogeneous, whereas α polymorphs was found to be energetically heterogeneous.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that the solute may not instantly crystallize while the saturation is satisfied at the surface of the droplet. Interestingly, the rate of nucleation and crystal growth determine the time to crystallization in the solution [48]. Indeed, gas bubbles can have a positive effect on crystallization, as commented by Nakamura [49], Matsumoto [50] and Deora [51].…”
Section: Morphologymentioning
confidence: 97%